PENERAPAN GOOD AGRICULTURE PRACTICES (GAP) PADA USAHATANI PADI MERAH ORGANIK - Afdila Syifa'atus Shofi; Titin Agustina; Sri Subekti (University of Jember, 2019)
Sirtanio Rural Agriculture Training Center (P4S) is an organic farming training institution in Banyuwangi. The technological innovations introduced by P4S are outlined in the form of Standard Operational Procedure (SOP) to make it easier for farmers to adopt organic farming systems. The purpose of this study was to determine: (1) the level of application of GAP SOP on organic red rice farming farmers participating in Sirtanio P4S in Banyuwangi, (2) the factors that influence farmers decisions in the implementation of organic red rice farming GAP SOP for farmers participating in Sirtanio P4S in Banyuwangi, and (3) the correlation between the application of GAP SOP on organic rice farming of participant farmersin Sirtanio P4S in Banyuwangi towards organic red rice production. The determination of the study area uses the purposive method, namely in the Village Sumberarum District Songgon Banyuwangi Regency East Java, Indonesia. The research method uses descriptive and analytical methods. The sampling technique for this study is total sampling. The data retrieval uses interview, observation and document analysis methods. The results showed that (1) the level of application of organic farming in Songgon District as a whole was high (64,52%); (2) the factors that significantly influence the decision making of organic red rice farmers in adopting organic GAP SOP as recommended were age, income, and land ownership status; and (3) there was a significant relationship between the application of organic GAP SOP to rice production organic red in Sumberarum Village.